Avenues to Characterize the Interactions of Extended N‐Glycans with Proteins by NMR Spectroscopy: The Influenza Hemagglutinin Case. Issue 46 (17th October 2018) - Fernández de Toro, Beatriz; Peng, Wenjie; Thompson, Andrew J.; Domínguez, Gema; Cañada, F. Javier; Pérez‐Castells, Javier; Paulson, James C.; Jiménez‐Barbero, Jesús; Canales, Ángeles
Abstract: Long‐chain multiantenna N‐glycans are extremely complex molecules. Their inherent flexibility and the presence of repetitions of monosaccharide units in similar chemical environments hamper their full characterization by X‐ray diffraction or standard NMR methods. Herein, the successful conformational and interaction analysis of a sialylated tetradecasaccharide N‐glycan presenting two LacNAc repetitions at each arm is presented. This glycan has been identified as the receptor of the hemagglutinin protein of pathogenic influenza viruses. To accomplish this study, a N‐glycan conjugated with a lanthanide binding tag has been synthesized, enabling analysis of the system by paramagnetic NMR. Under paramagnetic conditions, the NMR signals of each sugar unit in the glycan have been determined. Furthermore, a detailed binding epitope of the tetradecasaccharide N‐glycan in the presence of HK/68 hemagglutinin is described. Abstract : Tagging the flu : Conformational and interaction analysis of a sialylated tetradecasaccharide N‐glycan with two LacNAc repetitions at each arm is presented. This glycan has been identified as the receptor of the hemagglutinin protein of pathogenic influenza viruses. An N‐glycan conjugated with a lanthanide binding tag was synthesized, enabling analysis of the system by paramagnetic NMR spectroscopy.